LY3022855, an anti–colony stimulating factor-1 receptor (CSF-1R) monoclonal antibody, in patients with advanced solid tumors refractory to standard therapy: phase 1 dose-escalation trial - Dowlati, Afshin; Harvey, R. Donald; Carvajal, Richard D.; Hamid, Omid; Klempner, Samuel J.; Kauh, John Sae Wook; Peterson, Daniel A.; Yu, Danni; Chapman, Sonya C.; Szpurka, Anna M.; Carlsen, Michelle; Quinlan, Tonya; et al. (Investigational new drugs, 2021)
Summary Background Tumor-associated macrophages (TAMs) promote tumor growth, metastasis, and therapeutic resistance via colony-stimulating factor-1 (CSF-1), acting through CSF-1 receptor (CSF-1R) signaling. This phase 1 study determined the safety, tolerability, pharmacokinetics-pharmacodynamics, immunogenicity, and efficacy of the anti–CSF-1R antibody LY3022855 in solid tumors. Methods Patients with advanced solid tumors refractory to standard therapy were enrolled and treated in 2 dosing cohorts: weight-based (part A) and non–weight-based (part B). Part A patients were assigned to intravenous (IV) dose-escalation cohorts: 2.5 mg/kg once per week (QW), 0.3 mg/kg QW, 0.6 mg/kg QW, 1.25 mg/kg once every 2 weeks (Q2W) and 1.25 mg/kg QW doses of LY3022855. Non–weight-based doses in part B were 100 mg and 150 mg IV QW. Results Fifty-two patients (mean age 58.6 ± 10.4 years) were treated with ≥1 dose of LY3022855 (range: 4–6). Five dose-limiting toxicities (left ventricular dysfunction, anemia, pancreatitis, rhabdomyolysis, and acute kidney injury) occurred in 4 patients. The non–weight-based 100 mg QW dose was established as the RP2D. The most common treatment-emergent adverse events were increase in liver function variables, fatigue, nausea, vomiting, diarrhea, anorexia, pyrexia, increased lipase, amylase, and lactate dehydrogenase. Clearance decreased with increasing dose and weight-based dosing had minimal effect on pharmacokinetics. Serum CSF-1, and IL-34 levels increased at higher doses and more frequent dosing, whereas TAMs and CD14dimCD16bright levels decreased. Three patients achieved stable disease. No responses were seen. Conclusions LY3022855 was well tolerated and showed dose-dependent pharmacokinetics-pharmacodynamics and limited clinical activity in a heterogenous solid tumor population. ClinicalTrials.gov ID NCT01346358 (Registration Date: May 3, 2011).